Media-Induced Secondary Traumatic Stress: The Case of the Kahramanmaras Earthquake in Turkey - Kiraz Demir, Selin; İnci Namli, Nur (European Journal of Mental Health, 2024)
Introduction: Trauma manifests in a variety of ways and disrupts the lives of individuals. This is particularly the case in an age when communication technologies are permeating everyday practices, and mass media is an essential means of communication. A review of the international literature on disasters reveals that the measurement tools used in the research on the association between Secondary Traumatic Stress (STS) and the media are limited.Aims: The main aim of this study is to measure the STS levels in the audience of the media content regarding the Kahramanmaras-centered earthquake and to examine the factors associated with it.Methods: First, a measurement tool on the subject was developed, and then its psychometric properties were investigated. Exploratory factor analysis, confirmatory factor analysis, validity, and reliability analyses were conducted throughout the studies (N = 30 for Study I; N = 265 for Study II; N = 283 for Study III).Results: A 17-item, four-factor (intrusion, anxiety, media distrust, and avoidance), valid and reliable scale was created. Moreover, depression was found to have a partial mediating effect on the significant relationship between media exposure related STS and psychological well-being (β = –.22, SE = .027, 95% CI [–.25, –.19]).Conclusions: The results revealed the multi-dimensional impact of STS on people indirectly exposed to trauma as well as the uniqueness of the scale.